PEMBELAJARAN KETERAMPILAN MENULIS CERPEN MENGGUNAKAN METODE QUANTUM LEARNING DENGAN HIPNOSIS SEBAGAI UPAYA PENGUATAN KARAKTER UNGGUL - Mimin Sahmini; Via Nugraha (Jurnal Semantik, 2022)
This research is motivated by the low literacy skills of students in Indonesia. As reported by El-Fikri (2018) that Indonesian people's interest in reading and writing is still low, even in the ASEAN region Indonesia's ranking in this aspect is only above Cambodia and Laos. If the literacy problem is left unchecked and there is no movement that is able to target the right target to make the community and students aware, then this problem will continue to intertwine and get worse. This is a setback for the Indonesian people. Students who are creative in writing will grow into students who have a future. The results of his writings can be a motivation for him to be more creative in writing. The purpose of this study was to find out the description and steps of learning to write using the quantum learning method with hypnosis as an effort to strengthen character through moral messages in the short stories written. This study uses a qualitative descriptive method, in this study the researcher describes the picture of learning to write short stories using the quantum learning method with hypnosis and describes the results of the analysis of character values through moral messages in their values. The results of this study produce students who are skilled in writing and have superior characters.